Histone Acetylation and Modifiers in Renal Fibrosis - Shen, Fengchen; Zhuang, Shougang (Frontiers in Pharmacology, 2022)
Histones are the most abundant proteins bound to DNA in eukaryotic cells and frequently subjected to post-modifications such as acetylation, methylation, phosphorylation and ubiquitination. Many studies have shown that histone modifications, especially histone acetylation, play an important role in the development and progression of renal fibrosis. Histone acetylation is regulated by three families of proteins, including histone acetyltransferases (HATs), histone deacetylases (HDACs) and bromodomain and extraterminal (BET) proteins. These acetylation modifiers are involved in a variety of pathophysiological processes leading to the development of renal fibrosis, including partial epithelial-mesenchymal transition, renal fibroblast activation, inflammatory response, and the expression of pro-fibrosis factors. In this review, we summarize the role and regulatory mechanisms of HATs, HDACs and BET proteins in renal fibrosis and provide evidence for targeting these modifiers to treat various chronic fibrotic kidney diseases in animal models.